Peracangan Kemasan makanan Ringan Kacang Sihobuk Produksi â€œUD. TADODOâ€ sebagai Media promosi - Sinaga, Rommel; Simangunsong, Sahban (Politeknik Negeri Media Kreatif)
In recent years the development of the business world has progressed quite rapidly, in order to survive the company must have an effective marketing solution, one of which is by doing a packaging design.Â Indirect packaging is very influential in a product marketing because packaging is not only a company's professionalism, even packaging is also used as a branding / corporate identity to increase buyer interest.How to design packaging for processed yakobuk beans. TADODO in order to become a corporate identity and be able to become a solution in marketing. With the packaging design, people will get to know UD. TADODO as a business that produces sihobuk beans thus increasing buyer interest.